Dinamka psikhomotornykh funktsii studentov v protsesse kontrol'nykh ispytanii v bege na razlichnye distantsii - Mahadme, A. -K.; Gerba Taha, H. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The present paper represents the results of investigation devoted to the analyses of students psychomotoric functions' dynamics at the process of preparing and caring out the control testing 100, 400 and 1500 m running. The emergency reactions to the moving object, maximal and dosen effort had been studied. It became possible to reveal the peculiarities of students emotional agitation before the beginning of a working up, as well as the students mobilizational readiness before the start and their psychical fatigue after a heat in dependence on the loads value.